Role of PP2Cα in cell growth, in radio- and chemosensitivity, and in tumorigenicity - Lammers, Twan (BioMed Central, 2007)
BACKGROUND: PP2Cα is the representative member of the type 2C family of protein phosphatases, and it has recently been implicated in the regulation of p53-, TGFβ-, cyclin-dependent kinase- and apoptosis-signaling. To investigate the role of PP2Cα in cell growth and in radio- and chemosensitivity, wild type and PP2Cα siRNA-expressing MCF7 cells were subjected to several different viability and cell cycle analyses, both under basal conditions and upon treatment with radio- and chemotherapy. By comparing the growth of tumors established from both types of cells, we also evaluated the involvement of PP2Cα in tumorigenesis. RESULTS: It was found that knockdown of PP2Cα did not affect the proliferation, the clonogenic survival and the membrane integrity of MCF7 cells. In addition, it did not alter their radio- and chemosensitivity. For PP2Cα siRNA-expressing MCF7 cells, the number of cells in the G0/G1 phase of the cell cycle was reduced, the induction of the G1 block was attenuated, the number of cells in G2/M was increased, and the induction of the G2 block was enhanced. The tumorigenic potential of PP2Cα siRNA-expressing MCF7 cells was found to be higher than that of wild type MCF7 cells, and the in vivo proliferation of these cells was found to be increased. CONCLUSION: Based on these findings, we conclude that PP2Cα is not involved in controlling cell growth and radio- and chemosensitivity in vitro. It does, however, play a role in the regulation of the cell cycle, in the induction of cell cycle checkpoints and in tumorigenesis. The latter notion implies that PP2Cα may possess tumor-suppressing properties, and it thereby sets the stage for more elaborate analyses on its involvement in the development and progression of cancer.